SERAPAN HARA N DAN P PADA TANAMAN CIPLUKAN (Physalis angulata L.) YANG DIPERLAKUKAN DENGAN BERBAGAI MACAM PUPUK KANDANG - Septiana, Nurul Aini; Kusmarwiyah, Kusmarwiyah; Silawibawa, I Putu (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
This study was aimed to determine the influence of various kinds of manure on N and P uptake on Golden berry (Physalis angulata L.). The experiment was conducted in a plastic house in Terong Tawah, Subistrict of Labuapi, West Lombok regency. The experiment was set up using a Completely Randomized Design (CRD) with 6 treatments namely A0 (control), A1 (chicken manure), A2 (goat-manure, A3 (buffalo manure), A4 (horse manure), and A5 (cattle manure) which were repeated 3 times. The results showed that application of manures significantly affect fresh weight of stover, the dry weight of stover, N and P uptake. The application of buffalo manure tend to have the highest nutrients uptake.